Chitosan oligosaccharide, chitosan oligosaccharide composite nanoparticle, preparation method and application
The oligomeric chitosaccharides were prepared by ultrasonic-microwave synergistic complex enzyme enzymatic method and assembled with zein to form composite nanoparticles, which solved the problems of low enzymatic chitosaccharide efficiency and unstable product quality in the prior art, and achieved efficient and stable preparation of chitosaccharides and improved nanocarrier performance.
Patent Information
- Application Number
- CN202311413417.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art has problems in the enzymatic process of chitosan, such as low degradation efficiency, wide distribution of product molecular weight, and easy to lead to Maillard reaction and browning, resulting in high preparation cost and unstable quality of chitosan.
Ultrasonic-microwave synergistic complex enzyme enzymatic method was used to prepare chitooligosaccharides, and oligooligosaccharide composite nanoparticles were assembled with zein by anti-solvent co-precipitation method.
It improves the yield and quality of oligomeric chitin oligosaccharides, enhances the stability and antioxidant activity of nanocarriers, imparts the dual characteristics of hydrophilic and hydrophobic properties of nanoparticles, and is suitable for the sustained release of hydrophilic and hydrophobic drugs.
Smart Images

Figure CN119899285A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polysaccharide preparation and nano-carrier, and specifically relates to oligochitosan, oligochitosan composite nano-particles, and a preparation method and application thereof. Background Art
[0002] Chitosan (CS) is an extract from crustaceans such as shrimp, crab, and insects. It is the only cationic polysaccharide in nature that is formed by glucosamine and a small amount of acetylglucosamine connected by β-1,4 glycosidic bonds. Due to its good physical and chemical properties such as degradability, biocompatibility, antibacterial and film-forming properties, chitosan has become an important biomaterial and is widely used in agriculture, industry, food, medicine and other fields. However, the solubility of chitosan is poor, which limits its application to a certain extent. Chitooligosaccharide (COS) is a degradation product of chitosan, composed of oligosaccharides with a polymerization degree of 2-20, containing a large number of hydroxyl groups and amino groups, and has better water solubility than chitosan. It also has biological activities such as anti-tumor, antioxidant, antibacterial, and immunomodulatory. In particular, chitooligosaccharides with a polymerization degree of 2 to 7 also have good blood-brain barrier penetration ability, and have great application potential in the field of functional foods and biomedicine.
[0003] There are chemical, physical, and bio-enzyme methods for preparing chitosan. Among them, the enzymatic method is mild, can effectively maintain the biological activity of chitosan oligosaccharides, and is the most widely used, but its degradation of chitosan is limited, and the enzymatic hydrolysis products are difficult to control, have a wide molecular weight distribution, are prone to Maillard reaction and cause browning, and have high production costs. Therefore, the green and efficient preparation technology of chitosan oligosaccharides is still a technical problem that needs to be solved in production.
[0004] Chitosan oligosaccharide contains amino, hydroxyl and other functional groups in its molecular structure, which can be modified by hydrophobic small molecules to form amphiphilic polymers, which can easily self-assemble into polymer nanoparticles in water. Moreover, chitosan oligosaccharide modified nanocarriers also have the ability to cross the blood-brain barrier, and can be used in the construction of nano-delivery carriers, making it easier to achieve targeted transport and controlled release. Compared with protein nanocarrier materials, the formed nanoparticles have smaller particle sizes and stronger stability.
[0005] The invention prepares oligochitosan by ultrasound-microwave synergistic composite enzyme hydrolysis, and uses the oligochitosan composite nanoparticles as raw materials, which is of great significance for improving the yield and quality of oligochitosan, improving the stability and targeted delivery capacity of oligochitosan nanocarriers, and broadening the application range of oligochitosan. The invention is simple to operate, economical and practical, and has extremely broad market prospects. Summary of the invention
[0006] The purpose of the present invention is to provide a chitosan oligosaccharide, a chitosan oligosaccharide composite nanoparticle, a preparation method and an application thereof in view of the deficiencies in the prior art. The present invention can obtain a chitosan oligosaccharide with a narrow molecular weight distribution, a high yield of chitosan oligosaccharide, and a simple and easy preparation process; the present invention also improves the performance of the chitosan oligosaccharide composite nanoparticle, which has a small particle size, high stability, and high antioxidant activity, and gives the particle a dual hydrophilic and hydrophobic property, which can simultaneously meet the sustained release of hydrophilic and hydrophobic drug molecules, and has a better application prospect than conventional nanoparticles.
[0007] The invention provides a chitosan oligosaccharide, characterized in that the chitosan oligosaccharide has a polymerization degree of 2 to 6 and an average molecular weight of 350 to 1000 Da.
[0008] The present invention provides a method for preparing chitosan oligosaccharide, comprising the following steps:
[0009] A1) dissolving the chitosan raw material in an acetate buffer solution, and treating the solution in an ultrasound-microwave synergistic reaction workstation to obtain a chitosan solution with a concentration of 10 to 20 g / L;
[0010] A2) adding the complex enzyme to the chitosan solution obtained in step A1), mixing evenly, adjusting the pH range, keeping the temperature for a certain period of time for enzymolysis, killing the enzyme after the enzymolysis, cooling to room temperature, and adjusting the pH to 8-12 to obtain an enzymolysis solution;
[0011] A3) filtering the enzymatic hydrolyzate obtained in step A2) to remove the residue, concentrating the filtrate in vacuum to a viscous state, adding 2 to 3 times the volume of anhydrous ethanol, and then placing it in a refrigerator to stand overnight. The next day, filtering to remove the residue, concentrating the supernatant, and vacuum freeze-drying to obtain oligochitosan oligosaccharides.
[0012] Preferably, in step A1), the ultrasonic-microwave synergistic reaction treatment conditions are: microwave power 100-300 W, ultrasonic power 150-450 W, and treatment time 5-25 min.
[0013] Preferably, in step A2), the complex enzyme is composed of α-amylase and chitosanase in a mass ratio of 1:1-4, and the mass volume ratio of the added amount of the complex enzyme to the chitosan solution is 1-3 g / L.
[0014] Preferably, in step A2), the pH value range is 4 to 6, the heat preservation enzymolysis temperature is 45 to 60° C., and the enzymolysis time is 3 to 8 hours.
[0015] The invention provides a composite nanometer particle of oligochitosan oligosaccharide, which is characterized in that it is formed by assembling the oligochitosan oligosaccharide or the oligochitosan oligosaccharide prepared by the preparation method and zein.
[0016] Preferably, it is characterized in that the average particle size of the oligochitosan oligosaccharide composite nanoparticles is 80 to 250 nm and the potential is 41 to 50 mV.
[0017] The present invention provides a method for preparing chitosan oligosaccharide nanoparticles, comprising the following steps:
[0018] B1) weighing the chitosan oligosaccharide according to claim 1 or the chitosan oligosaccharide prepared by the preparation method according to any one of claims 2 to 5, and fully dissolving it in distilled water, and then adding anhydrous ethanol to obtain an ethanol solution of chitosan oligosaccharide;
[0019] B2) mixing the oligochitosan ethanol solution obtained in step B1) with zein in a certain mass ratio, stirring evenly, to obtain a glycoprotein mixture;
[0020] B3) adjusting the pH value of the glycoprotein mixture obtained in step B2) to a range of 2 to 9, magnetically stirring the mixture in the dark at room temperature for a certain period of time, then quickly pouring 2 to 3 times the volume of distilled water, stopping stirring, and obtaining a nanoparticle dispersion;
[0021] B4) The nanoparticle dispersion obtained in step B3) is concentrated in vacuum at 30-50° C. to remove ethanol, and then centrifuged to remove large particles. The supernatant is freeze-dried to obtain oligochitosan oligosaccharide composite nanoparticles.
[0022] Preferably, in step B1), the concentration of the oligochitosan in the oligochitosan ethanol solution is 0.1-2 mg / mL, and the final concentration of ethanol is 60%-90%.
[0023] Preferably, in step B2), in the glycoprotein mixture, the mass ratio of oligochitosan to zein is 1:5-100.
[0024] Preferably, in step B3), the pH adjustment range is 3 to 5; the rotation speed of the magnetic stirring is 500 to 1000 rpm / min, and the stirring time is 10 to 40 min.
[0025] The present invention also provides the use of the oligochitosan described in the above technical solution, or the oligochitosan prepared by the preparation method, or the oligochitosan composite nanoparticles, or the oligochitosan composite nanoparticles prepared by the preparation method in food, health products, and drug carriers.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention uses ultrasound-microwave synergistic composite enzyme to prepare oligochitosan oligosaccharides, and uses them as raw materials, and uses anti-solvent coprecipitation method to assemble oligochitosan oligosaccharide composite nanoparticles with proteins under the driving force of hydrogen bonds and electrostatic interaction, which can not only solve the browning problem of oligochitosan oligosaccharides, simplify the preparation process of oligochitosan oligosaccharides, improve the yield and quality of oligochitosan oligosaccharides, but also improve the stability and antioxidant function of oligochitosan oligosaccharides. The prepared oligochitosan oligosaccharide composite nanoparticles have higher antioxidant activity than oligochitosan oligosaccharides, and have small particle size, high stability, and dual characteristics of hydrophilicity and hydrophobicity, which can simultaneously meet the sustained release of hydrophilic and hydrophobic drug molecules, and have better application prospects compared with conventional nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a graph showing the effect of the complex enzyme, α-amylase, and chitosanase on the enzymatic hydrolysis efficiency of chitosan in Example 1;
[0029] Figure 2 The TLC chart (A) and HPLC chart (B) of the chitosan oligosaccharide of Example 1;
[0030] Figure 3 This is the result diagram of the effect of the mass ratio of oligochitosan to zein on the particle size and PDI of oligochitosan composite nanoparticles;
[0031] Figure 4 This is the result diagram of the effect of the mass ratio of oligochitosan and zein on the Zeta potential of oligochitosan composite nanoparticles;
[0032] Figure 5 This is the FTIR image of the oligochitosan oligosaccharide composite nanoparticles and their components in Example 3;
[0033] Figure 6 This is a scanning electron microscope image of the oligochitosan oligosaccharide composite nanoparticles of Example 3;
[0034] Figure 7 The figure is a comparison chart of the yield of oligochitosan oligosaccharides obtained by different preparation methods;
[0035] Figure 8 This is a diagram showing the effect of the oligochitosan composite nanoparticles of the present invention on improving the antioxidant activity of the oligochitosan of the present invention. DETAILED DESCRIPTION
[0036] The following is a detailed description of the embodiments of the present invention in conjunction with the accompanying drawings. It should be noted that this embodiment is descriptive and not restrictive, and the protection scope of the present invention cannot be limited by this. Unless otherwise specified, all detection techniques and methods in the following embodiments are conventional methods; the test materials used in the following embodiments are conventional chemical reagents and biochemical reagents.
[0037] Main materials and reagents: chitosan (Shanghai Aladdin Biochemical Technology Co., Ltd.); chitosanase (100,000 U / g, Shanghai Yuanye Biotechnology Co., Ltd.); α-amylase (1500 U / g, Shanghai Jizhi Biochemical Technology Co., Ltd.); zein (Shanghai Yuanye Biotechnology Co., Ltd.); glucosamine hydrochloride standard sample (purity 99%, Sigma, USA); anhydrous ethanol, sodium hydroxide, hydrochloric acid, sodium chloride, ninhydrin, FeSO4, etc. (Sinopharm Chemical Reagent Co., Ltd., analytical reagents); DPPH free radical scavenging ability kit (Nanjing Jiancheng Bioengineering Institute); ABTS free radical scavenging ability test kit (Beijing Solebold Technology Co., Ltd.); acetonitrile (chromatographic grade, Merck, Germany);
[0038] Main instruments and equipment: XO-SM400 ultrasonic microwave synergistic reaction workstation (Nanjing Xianou Instrument Manufacturing Co., Ltd.); high performance liquid chromatograph (with differential detector, Agilent Technologies, USA); rotary evaporator (Shanghai Xiande Experimental Instrument Co., Ltd.); magnetic stirrer (Shanghai Sile Instrument Co., Ltd.); refrigerated centrifuge (Hunan Xiangyi Laboratory Instrument Development Co., Ltd.); particle size-Zeta potential analyzer (Zetasizer Nano-ZS90, Malvern, UK); transmission electron microscope (Hitachi HT7700, Japan); desktop constant temperature oscillator (Tianjin Ounuo Instrument Co., Ltd.); microplate reader (Thermo Scientific Multiskan GO, USA); vacuum freeze dryer (Nanjing Zaizhi Automation Equipment Co., Ltd.); pH meter (Mettler Toledo Technology (China) Co., Ltd.).
[0039] Example 1
[0040] A method for preparing chitosan oligosaccharide comprises the following steps:
[0041] A1) dissolving 10 g of chitosan in 1000 mL of acetate buffer and treating in an ultrasound-microwave synergistic reaction workstation. The ultrasound-microwave synergistic reaction treatment conditions are: microwave power 250 W, ultrasonic power 300 W, and treatment time 10 min to obtain a chitosan solution with a concentration of 10 g / L;
[0042] A2) weighing 2.5 g of a composite enzyme consisting of α-amylase and chitosanase (mass ratio 1:1), adding the mixture to the chitosan solution, mixing well, adjusting the pH value to 5, and performing enzymolysis at 55° C. for 5 h. After the enzymolysis, inactivating the enzyme at 90-95° C. for 10 min, cooling the mixture to room temperature, and then adjusting the pH value to 8 to obtain an enzymolysis solution;
[0043] A3) The enzymatic hydrolysate is filtered to remove the residue, the filtrate is vacuum concentrated to a viscous state, 2 to 3 times the volume of anhydrous ethanol is added, and then placed in a refrigerator to stand overnight. The next day, the residue is filtered to remove the residue, the supernatant is concentrated, and vacuum freeze-dried to obtain oligochitosan.
[0044] This embodiment uses reducing sugar content as an indicator to compare the effects of compound enzyme (1:1) with α-amylase and chitosanase on the enzymatic hydrolysis of chitosan.
[0045] Determination of reducing sugar content: Prepare a standard curve with the absorbance value (Y) at 540nm as the ordinate and the concentration of glucosamine hydrochloride (mg / mL) as the abscissa (X). Take 1mL of chitosan enzymatic hydrolyzate and, according to the standard curve equation (Y=0.4711x-0.0315, R 2 =0.9985) to calculate its reducing sugar content.
[0046] The results are as follows Figure 1 As shown, the enzymatic hydrolysis efficiency of the composite enzyme (the mass ratio of α-amylase to chitosanase is 1:1) is 25.87% higher than that of α-amylase and 91.09% higher than that of chitosanase. It can be seen that the composite enzyme composed of α-amylase and chitosanase used in the present invention has obvious advantages in enzymatic hydrolysis of chitosan.
[0047] The components of the chitosan oligosaccharide prepared in this embodiment were analyzed by thin layer chromatography (TLC) and high performance liquid chromatography (HPLC), and the average molecular weight was determined by the acetylacetone method.
[0048] TLC analysis: Prepared chitosan oligosaccharide sample into 1% solution, take 2μL with capillary pipette and spot on high-efficiency silica gel plate, the spacing between each spot is 0.5cm, the distance from the bottom is 1.0cm, put the spotted silica gel plate into the chromatography cylinder with the development system of isopropanol: ammonia water: water = 15: 7.5: 1, take it out after the upward development, and blow it dry with a hair dryer. Spray 0.5% ninhydrin color developer on the silica gel plate, place it in a 100℃ oven for 5min heating and color development, and the purple-red color points are various sugars.
[0049] HPLC analysis: HILIC-Z (2.1×100 mm, 2.7 μm) chromatographic column; mobile phase A: water + 0.3% NH4OH (20%), B: acetonitrile + 0.3% NH4OH (80%); gradient conditions: 0-10 min 50% A-50% B, 10-15 min 60% A-40% B, 15-16 min 20% A-80% B; flow rate 0.6 ml / min; injection volume 1 μL, sample concentration: 10 mg / mL, evaporative light scattering detector, temperature 60°C.
[0050] Molecular weight determination of chitosan oligosaccharide: a standard curve was drawn with the absorbance value (Y) at 525 nm as the ordinate and the concentration of glucosamine hydrochloride (mg / mL) as the abscissa (X); freeze-dried chitosan oligosaccharide was prepared into a 1 mg / mL aqueous solution, and the standard curve was prepared according to the standard curve equation (Y = 0.0225x + 0.0961, R 2 =0.9982) to calculate the concentration c of D-glucosamine hydrochloride, and then calculate its average molecular weight according to the following formula.
[0051] M=m×V×215.6 / (C×1000)
[0052] Where: M is the average molecular weight, Da; m is the sample mass, g; V is the sample volume, mL; C is the concentration of D-glucosamine hydrochloride, μg / mL.
[0053] The results of TLC (A) and HPLC (B) analysis of the chitosan oligosaccharide prepared in this example are as follows: Figure 2 As shown, the main components of the prepared product are chitobiose, chitotriose, chitotetraose, chitopentaose and chitohexaose, and the polymerization degree thereof is 2 to 6; the average molecular weight is 993.5 Da.
[0054] Example 2
[0055] The preparation of oligochitosan composite nanoparticles (the mass ratio of oligochitosan to zein is 1:10) comprises the following steps:
[0056] B1) 20 mg of the chitosan oligosaccharide prepared in Example 1 was dissolved in 4 mL of distilled water, and then 16 mL of anhydrous ethanol solution was added to make the final concentration of ethanol 80%, to obtain a chitosan oligosaccharide ethanol solution with a final concentration of 1 mg / mL;
[0057] B2) mixing the oligo-chitosan ethanol solution with 200 mg of zein, stirring evenly to obtain a glycoprotein mixture;
[0058] B3) adjusting the pH of the glycoprotein mixture to 4 with an acid, and stirring the mixture at 800 rpm / min for 30 min at room temperature in the dark, and then quickly pouring 3 times the volume of distilled water, stopping stirring, and obtaining a nanoparticle dispersion;
[0059] B4) The nanoparticle dispersion was concentrated under vacuum at 50° C. to remove ethanol, and then centrifuged at 10,000 r / min for 5 min to remove large particles, and the supernatant was freeze-dried to obtain oligochitosan oligosaccharide composite nanoparticles.
[0060] In the preparation process of this example, the effects of the mass ratio of oligochitosan to zein (1:10, 1:20, 1:50, 1:100, 1:5, 2:5, 3:5) on the particle size, potential and PDI of the composite nanoparticles were investigated. Figure 3 , Figure 4 The test results show that when the mass ratio of oligochitosan to zein is 2:5 and 3:5, the nanoparticles have a larger particle size, which is 392nm and 513nm respectively. In the range of 1:5-100, the prepared composite nanoparticles have good stability, the particle size is less than 121nm, the potential range is 41.5-46.9mV, and the PDI range is between 0.1 and 0.14; therefore, when preparing composite nanoparticles, 1:5-100 is the appropriate mass ratio of oligochitosan to zein, and the particle size of the composite nanoparticles prepared in the range of 1:10-100 is smaller than the control (zein nanoparticles).
[0061] Example 3
[0062] The preparation of oligochitosan composite nanoparticles (the mass ratio of oligochitosan to zein is 1:5) comprises the following steps:
[0063] B1) 20 mg of the chitosan oligosaccharide prepared in Example 1 was dissolved in 4 mL of distilled water, and then 16 mL of anhydrous ethanol solution was added to make the final concentration of ethanol 80%, to obtain a chitosan oligosaccharide ethanol solution with a final concentration of 1 mg / mL;
[0064] B2) mixing the oligo-chitosan ethanol solution with 100 mg of zein, stirring evenly to obtain a glycoprotein mixture;
[0065] B3) adjusting the pH of the glycoprotein mixture to 5 with an acid, and stirring the mixture in a dark place at room temperature with a magnetic stirrer at 800 rpm / min for 40 min, then quickly pouring 3 times the volume of distilled water, and stopping stirring to obtain a nanoparticle dispersion;
[0066] B4) The nanoparticle dispersion was concentrated in vacuo at 45° C. to remove ethanol, and then centrifuged at 8000 r / min for 10 min to remove large particles, and the supernatant was freeze-dried to obtain oligochitosan oligosaccharide composite nanoparticles.
[0067] In this embodiment, the possible interaction types in the formation of composite nanoparticles are analyzed by Fourier transform infrared spectroscopy, and the microstructure of the obtained chitosan oligosaccharide composite nanoparticles is observed by scanning electron microscopy (SEM).
[0068] The Fourier transform infrared (FTIR) spectrum of the composite nanoparticles and their components is shown in Figure 5 .Depend on Figure 5It can be seen that after adding oligochitosan, the FTIR spectrum of zein nanoparticles shifted from 3290.62cm-1 to 3286.78cm-1. This is due to the stretching vibration of the hydroxyl group, which indicates that there is hydrogen bond interaction during the formation of the composite nanoparticles. The absorption peak at 1650-1700cm-1 usually observed in zein belongs to the amide I band, and the peak at 1500-1550cm-1 belongs to the amide II band. It can be seen from the figure that the amide I band and amide II band of the composite nanoparticles shifted significantly during the formation process, indicating that electrostatic interaction occurred between oligochitosan and zein. Results of electron microscopy observations Figure 6 It can be seen that the composite nanoparticles of the present invention are spherical, have a smooth surface, and are evenly distributed in size.
[0069] Example 4
[0070] Stability analysis of oligochitosan composite nanoparticle dispersion.
[0071] Sample preparation: Same as Example 2, except that the nanoparticle dispersion obtained in step B3) is prepared for testing.
[0072] Thermal stability test method: 10 mL of nanoparticle dispersion was placed in a test tube and placed in a water bath at 30, 40, 50, 60, 70, or 80°C for 3 h. After the sample cooled to room temperature, the particle size, potential, and PDI of the sample were measured.
[0073] pH stability test method: The nanoparticle dispersion was adjusted to different pH values (2, 3, 4, 5, 6, 7) using 0.1 M HCl or 0.1 M NaOH. After being stored in a refrigerator at 4°C overnight, the particle size, potential and PDI of the sample were measured.
[0074] Salt stability test method: Mix 10 mL of nanoparticle dispersion with 10 mL of NaCl solution (0-400 mM) to obtain nanoparticle dispersions containing NaCl at different concentrations (0-200 mM). After storing them in a refrigerator at 4°C overnight, measure the particle size, potential and PDI of the samples.
[0075] It can be seen from the test results in Tables 1 to 3 that the composite nanoparticles are stable under the environmental conditions of 30 to 80° C., pH 2 to 5, and ≤200 mM NaCl concentration.
[0076] Table 1 Effect of temperature on the stability of oligochitosan composite nanoparticles
[0077]
[0078] Table 2 Effect of pH value on the stability of oligochitosan composite nanoparticles
[0079]
[0080] Table 3 Effect of salt ion concentration on the stability of oligochitosan composite nanoparticles
[0081]
[0082] The effects of the present invention are further illustrated by some experiments below.
[0083] The effect of the method of the present invention is evaluated by comparing the yield of oligochitosan oligosaccharides obtained by the (ultrasound-microwave synergistic complex enzyme) technology of the present invention with that of oligochitosan oligosaccharides obtained by other methods; the effect of the present invention is evaluated by comparing the antioxidant capacity of the oligochitosan oligosaccharide composite nanoparticles of the present invention with that of oligochitosan oligosaccharides of the same concentration.
[0084] 1. Sample Preparation
[0085] The preparation of oligochitosan using the ultrasound-microwave synergistic complex enzyme method (UMSE) of the present invention is the same as Example 1.
[0086] Preparation of oligochitosan oligosaccharide composite nanoparticles of the present invention: Same as Example 2.
[0087] Comparative Example 1: Preparation of oligochitosan by enzymatic hydrolysis (EE)
[0088] The difference from Example 1 is that step A1) is: 10 g of chitosan is dissolved in 1000 mL of acetate buffer to obtain a chitosan solution with a concentration of 10 g / L.
[0089] Comparative Example 2: Preparation of oligochitosan oligosaccharides by ultrasound-assisted enzymatic hydrolysis (UAE)
[0090] The difference from Example 1 is that step A1) is: 10 g of chitosan is dissolved in 1000 mL of acetate buffer, placed in an ultrasonic microwave synergistic reaction workstation, the microwave power is set to 0, the ultrasonic power is set to 300 W, and the treatment is performed for 10 min to obtain a chitosan solution with a concentration of 10 g / L.
[0091] Comparative Example 3: Preparation of oligochitosan oligosaccharides by microwave-assisted enzyme method (MAE)
[0092] The difference from Example 1 is that step A1) is: 10 g of chitosan is dissolved in 1000 mL of acetate buffer, placed in an ultrasonic microwave synergistic reaction workstation, the ultrasonic power is set to 0, the microwave power is set to 250 W, and the treatment is performed for 10 min to obtain a chitosan solution with a concentration of 10 g / L.
[0093] 2. Comparative analysis of the yield of oligochitosan in the present invention and comparative examples 1 to 3
[0094] The content of oligochitosan was determined by high performance liquid chromatography. The oligochitosan sample was hydrolyzed with concentrated hydrochloric acid to generate glucosamine hydrochloride, which was separated by an amino column and analyzed by a differential detector. The content of glucosamine hydrochloride was calculated by an external standard method to obtain the yield of oligochitosan in the sample. The detection method was the same as in Example 1.
[0095] The results of the yield test of oligochitosan obtained by different preparation methods are as follows: Figure 7 As shown, the yield of oligochitosan prepared by the UMSE method of the present invention is the highest, which is 85.21%, which is 27.36%, 20.06% and 14.99% higher than those of the oligochitosan prepared by the EE method (Comparative Example 1, 66.94%), UAE (Comparative Example 2, 70.97%) and MAE (Comparative Example 3, 74.10%), respectively, and has significant superiority.
[0096] 3. Analysis of the effect of the oligochitosan composite nanoparticles of the present invention on the antioxidant activity of the oligochitosan of the present invention
[0097] Determination of DPPH free radical scavenging rate: Take 1 mL of composite nanoparticle solution and oligochitosan solution with a chitosan mass concentration of 1 mg / L in different scale test tubes, add 1 mL of 0.2 mmol / L DPPH solution, shake well and place in the dark for 30 minutes, take the supernatant, and measure the absorbance at a wavelength of 517 nm by an automatic microplate reader. The DPPH free radical scavenging rate of composite nanoparticles and oligochitosan is calculated according to the following formula.
[0098] DPPH free radical scavenging rate (%) = [1-(A1-A2) / A0] × 100%
[0099] Where: A1 is the absorbance of the test group; A2 is the absorbance of the control group; A0 is the absorbance of the blank group.
[0100] ABTS·free radical scavenging rate determination: Take 0.2mL of composite nanoparticle solution and oligochitosan solution with a chitosan mass concentration of 1mg / L respectively, add 1.8mL of ABTS working solution, react in dark environment for 10min, and measure the absorbance at 734nm. Calculate the ABTS·free radical scavenging rate according to the formula.
[0101] ABTS·Free radical scavenging rate (%) = [1-(A1-A2) / A0] × 100%
[0102] Where: A1 is the absorbance of the test group; A2 is the absorbance of the control group; A0 is the absorbance of the blank group.
[0103] FRAP assay: 0.2 mL of composite nanoparticle solution and oligochitosan solution with a chitosan mass concentration of 1 mg / L were mixed with 1.8 mL of FRAP (acetic acid buffer, 300 mmol / L pH 3.6), TPTZ (10 mmol / L) and ferric chloride (20 mmol / L) at a ratio of 10:1:1 (V / V). The mixture was then incubated in a 37°C water bath for 10 min. The absorbance was measured at a wavelength of 593 nm using an automatic microplate reader. A standard curve was drawn using different concentrations of FeSO4 instead of the sample. According to the standard curve equation (Y = 0.0125X + 0.0617, R 2 =0.999) to calculate the total antioxidant capacity of the samples.
[0104] The results of DPPH free radical scavenging rate, ABTS free radical scavenging rate and ferric ion reducing ability (FRAP) are as follows Figure 6 As shown. Figure 8 It can be seen that the oligochitosan oligosaccharide and the oligochitosan oligosaccharide composite nanoparticles of the present invention both have high antioxidant activity, among which the oligochitosan oligosaccharide composite nanoparticles have higher antioxidant activity. The DPPH and ABTS free radical scavenging rates are increased by 10.95% and 15.92% respectively, and the FRAP is increased by 25.39mmol / L. It shows that the oligochitosan oligosaccharide composite nanoparticles prepared by the present invention can improve the antioxidant activity of oligochitosan oligosaccharides and have significant superiority.
[0105] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A chitosan oligosaccharide, characterized in that: The polymerization degree of the oligochitosan is 2-6, and the average molecular weight is 350-1000Da.
2. The method for preparing chitosan oligosaccharide according to claim 1, characterized in that: The steps include: A1) dissolving the chitosan raw material in an acetate buffer solution, and treating the solution in an ultrasound-microwave synergistic reaction workstation to obtain a chitosan solution with a concentration of 10 to 20 g / L; A2) adding the complex enzyme to the chitosan solution obtained in step A1), mixing evenly, adjusting the pH range, keeping the temperature for a certain period of time for enzymolysis, killing the enzyme after the enzymolysis, cooling to room temperature, and adjusting the pH to 8-12 to obtain an enzymolysis solution; A3) filtering the enzymatic hydrolyzate obtained in step A2) to remove the residue, concentrating the filtrate in vacuum to a viscous state, adding 2 to 3 times the volume of anhydrous ethanol, and then placing it in a refrigerator to stand overnight. The next day, filtering to remove the residue, concentrating the supernatant, and vacuum freeze-drying to obtain oligochitosan oligosaccharides.
3. The preparation method according to claim 2, characterized in that: In step A1), the ultrasonic-microwave synergistic reaction treatment conditions are: microwave power 100-300W, ultrasonic power 150-450W, and treatment time 5-25min.
4. The preparation method according to claim 2, characterized in that: In step A2), the complex enzyme is composed of α-amylase and chitosanase in a mass ratio of 1:1-4, and the mass volume ratio of the added amount of the complex enzyme to the chitosan solution is 1-3 g / L.
5. The preparation method according to claim 2, characterized in that: In step A2), the pH value ranges from 4 to 6, the incubation temperature for enzymolysis is 45 to 60° C., and the enzymolysis time is 3 to 8 hours.
6. A chitosan oligosaccharide composite nanoparticle, characterized in that: The oligochitosan is formed by assembling the oligochitosan according to claim 1 or the oligochitosan prepared by the preparation method according to any one of claims 2 to 5 with zein.
7. The oligochitosan oligosaccharide composite nanoparticles according to claim 6, characterized in that: The average particle size of the oligochitosan oligosaccharide composite nanoparticles is 80-250nm, and the potential is 41-50mV.
8. The method for preparing oligochitosan oligosaccharide composite nanoparticles according to claims 6 to 7, characterized in that: The steps include: B1) weighing the chitosan oligosaccharide according to claim 1 or the chitosan oligosaccharide prepared by the preparation method according to any one of claims 2 to 5, and fully dissolving it in distilled water, and then adding anhydrous ethanol to obtain an ethanol solution of chitosan oligosaccharide; B2) mixing the oligochitosan ethanol solution obtained in step B1) with zein in a certain mass ratio, stirring evenly, to obtain a glycoprotein mixture; B3) adjusting the pH value of the glycoprotein mixture obtained in step B2) to a range of 2 to 9, magnetically stirring the mixture in the dark at room temperature for a certain period of time, then quickly pouring 2 to 3 times the volume of distilled water, stopping stirring, and obtaining a nanoparticle dispersion; B4) The nanoparticle dispersion obtained in step B3) is concentrated in vacuum at 30-50° C. to remove ethanol, and then centrifuged to remove large particles, and the supernatant is freeze-dried to obtain oligochitosan oligosaccharide composite nanoparticles.
9. The preparation method according to claim 8, characterized in that: In step B1), the concentration of the oligochitosan in the oligochitosan ethanol solution is 0.1-2 mg / mL, and the final concentration of ethanol is 60%-90%.
10. The preparation method according to claim 8, characterized in that: In step B2), in the glycoprotein mixture, the mass ratio of oligochitosan to zein is 1:5-100.
11. The preparation method according to claim 8, characterized in that: In step B3), the pH adjustment range is 3 to 5; the rotation speed of the magnetic stirring is 500 to 1000 rpm / min, and the stirring time is 10 to 40 min.
12. Use of the oligochitosan according to claim 1, the oligochitosan prepared by the preparation method according to any one of claims 2 to 5, the oligochitosan composite nanoparticles according to any one of claims 6 to 7, and the oligochitosan composite nanoparticles prepared by the preparation method according to any one of claims 8 to 11 in food, health products, and drug carriers.
Citation Information
Cited By
Method for preparing chitosan oligosaccharide based on compound enzyme
CN120624581A
Instant silicon fertilizer and preparation method thereof
CN120965410A
Integrated system for preparing narrow-molecular-weight chitosan oligosaccharide through multi-physical-field online synergistic enzymolysis
CN122146465A